Theoretical studies of the function switch and mechanism of AceK as a highly active ATPase. Issue 72 (18th July 2016) - Qin, Jiajia; Tan, Hongwei; Li, Xichen; Chen, Guangju; Zheng, Jimin; Wang, Ye; Ma, Jianqiu; Jia, Zongchao
Abstract : As a multi-function enzyme, AceK integrates kinase, phosphatase and ATPase activities in a single active site and these functions are delicately regulated.. Abstract : As a multi-function enzyme, AceK integrates kinase, phosphatase and ATPase activities in a single active site. In contrast to most kinases, AceK exhibits unusually high ATPase activity compared to its kinase and phosphatase activities. The reason that AceK possesses such a high ATPase activity and its multi-function regulation are still elusive. In this work, we have employed DFT methods to exploit the ATP hydrolysis mechanism of AceK and revealed a dissociative pathway with an activation energy of only 17.85 kcal mol −1, which is highly favorable for ATPase activity. The high ATPase activity of AceK may play a role in producing ADP as a proton acceptor to fulfill its phosphatase function. Based on our calculation and structural analysis, binding with substrate ICDH causes a catalytically important residue, Asp477, to flip over and further suppress ATPase activity with a markedly increased activation energy of 21.68 kcal mol −1, thus favoring kinase or phosphatase activity. Our work has shed new light on the function switch and ATP hydrolysis mechanism of AceK.